2009
DOI: 10.1021/bc800500a
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis: A Biological Process Adapted in Drug Delivery, Therapy, and Imaging

Abstract: In many diseases, protease expressions are found deregulated when compared with them at the healthy states. The unique ability to hydrolyze protein amide bonds has made those deregulated proteases attractive biological triggers in drug development. Proteolysis has been widely applied in pro-drug design to achieve favorable pharmacokinetics. Controlled drug delivery systems are also reported by incorporating protease-sensitive motifs onto bio-, inorganic-, or organic- materials. In addition, protease responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 142 publications
1
89
0
2
Order By: Relevance
“…Proteinase K (also protease K or endopeptidase K) is a serine protease with broad substrate specificity [47]. Incubation of the dppzNB ligand with proteinase K for 4 h at 37 • C and analysis of the products generated by mass spectrometry showed that the amide bond in dppzNB undergoes digestion (see the electronic supplementary material, figure S9).…”
Section: Results and Discussion (A) Design Synthesis And General Aspmentioning
confidence: 99%
“…Proteinase K (also protease K or endopeptidase K) is a serine protease with broad substrate specificity [47]. Incubation of the dppzNB ligand with proteinase K for 4 h at 37 • C and analysis of the products generated by mass spectrometry showed that the amide bond in dppzNB undergoes digestion (see the electronic supplementary material, figure S9).…”
Section: Results and Discussion (A) Design Synthesis And General Aspmentioning
confidence: 99%
“…This area has considerable potential. Further examples are provided by Choi et al [3] and Law and Tung [4] .…”
Section: Opportunities For Drug Targetingmentioning
confidence: 99%
“…Despite their potential as therapeutic targets, however, a clinically useful agent has yet to materialise, despite several MMP inhibitors having been developed and evaluated in clinical trials [2] . More recently, attention has turned to the potential utility of MMPs as activators of targeted prodrug therapies [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Proteolysis is a simple hydrolytic process that separates two adjacent amino acid residues at the amide bond and is triggered by proteases. 15 Enzyme cleavable conjugates, containing enzyme-sensitive substrate, mainly take advantage of the selectivity and specificity of enzymes that are differentially active in the immediate environment of tumor cells.…”
Section: Introductionmentioning
confidence: 99%